A systematic review of bilingual experiences, labels, and descriptions in autism spectrum disorder research - Hantman, Rachel M.; Choi, Boin; Hartwick, Katie; Nadler, Zoe; Luk, Gigi (Frontiers in Psychology, 2023)
There is growing research on autism spectrum disorder (ASD) that examines linguistically diverse samples, increasing research generalizability as many individuals with ASD live in bilingual or multilingual communities. However, bilingualism is not a homogenous experience that can be easily categorized. By clarifying participants' language experiences, research findings can be more meaningful for clinicians and practitioners. In this systematic review, we document how the language experiences of samples with and without ASD were described in 103 peer-reviewed journal articles. We observed that language experiences were characterized using a wide range of labels and descriptions. Approximately half of the studies in this review reported participants' language acquisition history, and 64% of the studies defined language proficiency using standardized measures or parental reports. However, <20% of the studies reported daily language exposure and/or usage of the participants. The diversity in how participants' language experiences were characterized in research reflects the complexity of bilingualism. Yet, to further understand how ASD and bilingualism intersect across studies, to facilitate meta-science development, and to balance generalizability with specificity, reporting common characteristics of bilingual experiences is recommended.